Nitrogen uptake of nickel free austenitic stainless steel powder during heat treatment—an XPS study. (18th December 2014) - Weddeling, Anna; Lefor, Kathrin; Hryha, Eduard; Huth, Stephan; Nyborg, Lars; Weber, Sebastian; Theisen, Werner
<x xml:space="preserve">Abstract</x> In austenitic stainless steel nitrogen stabilizes the austenitic phase, improves the mechanical properties and increases the corrosion resistance. Nitrogen alloying enables to produce austenitic steels without the element nickel which is high priced and classified as allergy inducing. A novel production route is nitrogen alloying of CrMn‐prealloyed steel powder via the gas phase. This is beneficial as the nitrogen content can be adjusted above the amount that is reached during conventional casting. A problem which has to be overcome is the oxide layer present on the powder surface which impedes both the sintering process and the uptake of nitrogen. This study focuses on whether heat treatment under pure nitrogen is an appropriate procedure to enable sintering and nitrogen uptake by reduction of surface oxides. X‐ray photoelectron spectroscopy (XPS) in combination with scanning electron microscopy (SEM) and energy dispersive X‐ray spectrometry (EDS) are used to investigate the surface of powdered FeMn19Cr17C0.4N heat treated under nitrogen atmosphere. The analyses showed reduction of iron oxides already at 500 °C leading to oxide‐free metallic surface zones. Mn and Cr oxides are reduced at higher temperatures. Distinct nitrogen uptake was registered, and successful subsequent sintering was reached. Copyright © 2014 John Wiley & Sons, Ltd.